Effectiveness of Nordic Exercises in Subjects with Hamstring Strain. - Ranjith Kumar D.; Anitha A.; Ramana K.; Kamalakannan M. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Hamstring strains are the most prevalent muscle injuries reported in sport with a prevalence rate between 6% and 29% of all injuries reported. The symptoms of hamstring strains include pain, swelling, tenderness, bruising in the back of the thigh. There is an inadequacy of studies to support the efficacy of Nordic Exercise for hamstring strain. Purpose: To determine the effectiveness of Nordic exercise among subjects with hamstring strain. Materials and Methods: A Convenient sample of 80 subjects with hamstring strain were sorted out by the selection criteria and were randomly assigned into Nordic group and control group. The Nordic group was treated with Nordic exercises, while the Control group was treated with stretching and strengthening exercises on an odd-even randomization. The pre-test and post-test were obtained through "Functional assessment scale for acute hamstring injuries" (FASH). The entire study process was conducted from November 2022 to March 2023. Result: The study revealed that the Nordic exercise group showed reduction in hamstring strain and FASH score than the conventional group. The mean pre-test value for Nordic group was 57.00 and post-test value was 11.73, while the mean pre-test value for Control group was 52.61 and post-test value was 7.40. As a result, both groups have a significant increase in FASH. Conclusion: The study concluded that the Nordic exercises are more effective when compared to stretching and strengthening exercises for reduction of hamstring strain and increased functional activities.